Condições de otimidade para problemas de controle ótimo com condições de contorno funcionais - Ascona, John Frank Matos [UNESP] (2015)
In this work we consider the optimal control problem with functional boundary cons- traints. The purpose of this work is to propose optimality conditions for problems with functional boundary conditions involving continuously differentiable functions, considering the class of MP-pseudoinvex optimal control problems. Our results show that MP-pseudo- invexity is a sufficient condition of optimality for such problems